Nephroprotective effect of methanol extract of Moringa oleifera leaves on acute kidney injury induced by ischemia-reperfusion in rats (2020)
Background: Moringa oleifera is known to exhibit protection against oxidative damage due to its rich content of compounds with antioxidant activity. This study investigated the protective effect of the methanol extract of Moringa oleifera (MO) in a rat model of renal ischemia-reperfusion (IR) injury. Methods: Forty two wistar rats were randomly assigned to six groups of seven rats each, as follows: A, control group; B, sham-operated group; C, IR group; D, IR + low dose (200 mg/kg) MO; E, IR + high dose (400 mg/kg) MO and F, IR + Vitamin C (200 mg/kg). Unilateral ischaemia was induced by occluding the left renal artery for 45 minutes followed by rep erfusion up to 24 hours. Results: Moringa oleifera significantly (p<0.05) ameliorated IR-induced increases in malondialdehyde (MDA), protein carbon yls (PC) and advanced oxidation protein products (AOPP), while also decreasing serum BUN and Creatinine levels. Moreover, the low dose of MO caused reductions in renal NO and H2O2 levels, while increasing renal GPx and GST activities. Histopathology revealed marked improvement of tissue alterations induced by IR with both doses of MO. Conclusion: Overall, the methanol extract of M. oleifera effectively attenuated the deleterious effects of renal IR via alleviation of tissue oxidative stress.